Rebranding dan Citra Pelayanan Berimplikasi Kepuasan Pelanggan Jasa Pandu & Tunda Di Perairan Cilacap pada PT. Pertamina Port Logistics - Kwartama, Agung; Eka Wahyu, Krisma (Jurnal Manajemen dan Organisasi, 2025)
This study examines the impact of rebranding strategy and corporate image on service quality and customer satisfaction for pilotage and towage services in the Cilacap waters managed by PT. Pertamina Port Logistics. The primary objective of this research is to analyze how rebranding strategy and corporate image affect service quality and customer satisfaction, as well as the role of service quality as a mediator in these relationships. Using a quantitative design with a causal approach, data was collected through questionnaires and interviews with ship crews, as well as from secondary sources provided by the company. The sample consisted of 180 individuals from a population of 325, selected using Purposive Sampling and Simple Random Sampling techniques. Data analysis was performed using Structural Equation Modeling and helped by smart PLS aplication to model the causal relationships between variables. The findings indicate that both rebranding strategy and corporate image have a positive and significant effect on service quality and customer satisfaction, with corporate image having the greatest impact. Additionally, service quality acts as a significant mediator in the relationship between rebranding strategy and corporate image with customer satisfaction. These findings highlight the importance of enhancing corporate image and implementing effective rebranding strategies to improve service quality and customer satisfaction at PT. Pertamina Port Logistics. The study recommends focusing on the development of corporate image and rebranding strategies as strategic steps to enhance service outcomes and customer satisfaction.